The Study Of The Second Conflict In Sampang - Arnis Rachmadhani (Balai Penelitian dan Pengembangan Agama Semarang, 2013)
This research was basically based on qualitative study. It was the second conflict in Sampang, the rampage which exploded between some people who trying to block the Tajul Muluk’s followers and preventing them from going back to the Pondok Pesantren (Islamic Boarding House) of YAPPI in Bangil, Pasuruan. The data in this study was collected using three sorts of data collection techniques: interview, document analysis, and observation. It was done by using the conflict analysis method, from which the writer found out that this second incident appeared in Sampang is manifestation of latent conflict accumulation which is actually personal conflict complicated by some religious issues. The conflict is to be resolved by using both bureaucracy and cultural approaches.